Reducing carbon emissions in the dry port-seaport system: a shared transport approach - Wang, Xinhui; Wang, Xuefeng (Frontiers in Marine Science, 2025)
This research analyses the carbon emissions associated with a shared transport method within the dry port-seaport network, focusing on the realm of green transportation. Utilizing theoretical analysis and numerical examples, the study contrasts carbon emission levels across three distinct scenarios: shared transport, non-shared transport, and direct road transport. Numerical investigations are conducted to assess the environmental value sensitivity. Results indicate that when the total distance traveled by shippers exceeds that of shared transport, the milk-run transport approach can markedly decrease carbon emissions. Furthermore, transitioning from unimodal road transport to intermodal transport has the potential to yield significant carbon emission savings. This study offers a validated policy objective for fostering a more sustainable transportation system by promoting a modal shift from direct to shared transport.